Factors Influencing Parental Awareness about Newborn Screening - Franková, Věra; Dohnalová, Alena; Pešková, Karolína; Hermánková, Renata; O'Driscoll, Riona; Ješina, Pavel; Kožich, Viktor (International journal of neonatal screening, 2019)
Appropriate and timely education about newborn screening (NBS) helps to foster benefits such as prompt follow up, to promote parents' autonomy via informed consent and minimize the harms such as reducing the impact of NBS false-positive results. The aim of this study was to ascertain how mothers are informed about NBS in the Czech Republic and to identify the variables associated with awareness about NBS. The questionnaires evaluating awareness and its determinants were mailed to a random sample of 3000 mothers 3 months post-delivery. The overall response rate was 42%. We analysed 1100 questionnaires and observed that better awareness about NBS was significantly associated with age, parity, number of information sources, child health status, size of maternity hospital and an obstetrician as the source of prenatally obtained information. Although the majority of mothers (77%) in our study recalled being informed by a physician or nurse in the neonatal ward, results have revealed that over 40% of participants did not have sufficient awareness about the principal aspects of NBS. Several measures including seminars for healthcare providers and the development and distribution of new educational materials were adopted to improve parental education about NBS in the Czech Republic.